Diagnostic Value of Diffusion-Weighted MRI for Tumor Characterization, Differentiation and Monitoring in Pediatric Patients with Neuroblastic Tumors - Neubauer, Henning; Li, Mengxia; Müller, Verena Rabea; Pabst, Thomas; Beer, Meinrad (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose We explored the diagnostic value of diffusion-weighted MRI (DWI) for tumor characterization, differentiation and therapy monitoring in pediatric patients with extracranial neuroblastic tumors.Materials and Methods All 29 patients (14 girls, median age: 3 years) with neuroblastoma (NB, n = 19), ganglioneuroblastoma (GNB, n = 4) and ganglioneuroma (GN, n = 6) who had had at least one in-house DWI examination since 2005 were identified and retrospectively analyzed. Two independent blinded readers measured ADC values (unit: 10−3 mm2/s) and signal intensity ratios (SIRs) of the primary tumor and, if applicable, of the tumor after chemotherapy, metastases and tumor relapse.Results The pre-treatment ADC was 0.90 ± 0.23 in NB/GNB and 1.70 ± 0.36 in GN without overlap between the two entities for both readers, 0.67 ± 0.14 in metastases and 0.72 ± 0.18 in tumor relapse. With chemotherapy, mean ADC increased to 1.54 ± 0.33 in NB/GNB and to 1.23 ± 0.27 in metastases (p < 0.05). The median SIRs of various tumor lesions vs. liver, vs. muscle tissue and vs. adjacent tissue were significantly higher on DWI (range: 2.4 – 9.9) than on ce-T1w (range: 1.0 – 1.8, all p < 0.05). The coefficient of variation (CV) was ≤ 8.0 % for ADC and ≤ 16.4 % for signal intensity data.Conclusion Based on mean ADC, DWI distinguishes between NB/GNB and GN with high certainty and provides plausible quantitative data on tumor response to therapy. Lesion conspicuity, as measured by SIR, is superior on DWI, compared to ce-T1w. DWI as a noninvasive, radiation-free and widely available imaging technique should be an integral part of MR imaging for neuroblastic tumors and should undergo prospective evaluation in multicenter studies.Key Points Citation Format
Keywords: neuroblastoma; ganglioneuroblastoma; ganglioneuroma; therapy response; MR imaging; MR diffusion/perfusion